THE WOMAN STRUGGLE IN THE NOVEL JANE EYRE BY CHARLOTTE BRONTE AND ENTROK BY OKKY MADASARI: COMPARATIVE LITERATURE - Sarah, Rima; Pramita, Agry (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2022)
Culture and phenomena that exist in society can be known through novels. One of them is the phenomenon of women. This study discusses the woman struggle through two works of English and Indonesian literature, namely the novel Jane Eyre by Charlotte Bronte and the novel Entrok by Okky Madasari. These two novels tell about the life of the women character and their environment. This study uses the theory of feminist literary criticism to find feminist issues in the two novels that appear through the female characters. The method used is descriptive analysis using a qualitative approach. The data source is the novel Jane Eyre by Charlotte Bronte, published in 1847 by Smith, Elder & Co. in London, England, and Okky Madasari's novel Entrok published by Gramedia Pustaka Utama in 2010. The results of data analysis show that the female characters, namely Marni, Rahayu, and Jane Eyre have similarities in making efforts to equalize women through freedom of choice, education. , and work. However, there are also differences regarding the setting of place, time, and culture in the two novels.